Factors associated with the presence of cleft lip and / or cleft palate in Brazilian newborns - Bianca Machado Cruz Shibukawa; Gabrieli Patricio Rissi; Ieda Harumi Higarashi; Rosana Rosseto de Oliveira
Abstract Objectives: to analyze the trend and the associated factors with the presence of cleft lip and/or cleft palate in Brazilian newborns, in order to verify possible associations with maternal care and newborn factors. Methods: a cross-sectional and ecological study, involving all live births in Brazil, recorded in the Information System on Live Births from 2005 to 2016. Maternal and infant information were evaluated using trend analysis and odds ratio, with a 95% confidence interval. The analyses were performed using SPSS software. Results: we analyzed 17,800 live births with presence of cleft lip and/or cleft palate. The Brazilian prevalence rate was 0.51 / 1000 live births, with South and Southeast Regions registering higher rates than the national rate. There was an association with maternal age above 35 years old, with no partner, less than seven prenatal consultations, premature birth and cesarean section. About the factors of the newborn, being male, Apgar less than seven in the 1st and 5th minutes of life, low birth weight and white color were associated. Conclusions: Brazil has an increasing tendency for cleft lip and/or cleft palate (p=0.019), reinforcing the need to strengthen health care networks, providing adequate support for newborn with cleft lip and/or cleft palate and their families.